Agroecological mango business models in Kenya: A report of the assessment of the mango business models in Makueni Agroecological Living Landscapes (ALLs), Kenya - Chege, Christine G. Kiria; Onyango, Kevin; Bolo, Peter; Ndiwa, Aurillia M.; Wanyama, Rosina (2024)
Makueni is the leading County in Kenya in production of Mangoes. This is due to the County’s favourable environmental conditions and dedicated actors within the value chain. Since 2010, Kenya has progressively been producing about 650,000 metric tonnes of mango annually, with more than 20% coming from Makueni County. The thriving mango industry in Makueni County not only generates income for the value chain actors but also addresses food security, creates employment, and promotes sustainable agricultural practices. However, this commodity is affected by challenges involving market access, post-harvest losses and quality issues. Nevertheless, opportunities exist for the actors to optimize their gains from mango production, especially through leveraging on the most feasible business models that would properly and holistically link them to markets in the entire value chain. A rapid assessment of the mango value chain by the CGIAR Initiative on Agroecology showed that there exist three business models in Makueni ALL: (i) a public processor business model where farmer groups sell their produce to a public processing company through cooperatives, (ii) a private processor business model where farmer groups sell mangoes to the private sector processors, and (iii) the conventional business model where individual farmers sell to the wholesale market through brokers. The public and private processors business models were selected for further diagnosis and analysis given their potential for a wider economic, social, and environmental impact on the local community. A comprehensive assessment of their customer segments, value propositions, channels and customer relations, income streams, key resources, key activities, as well as key partners and cost structures was conducted using the Business Model Canvas (BMC). In addition, the Business Agroecological Criteria Tool (B-ACT) was used to assess the level of integration of agroecological principles in the two business models. A Cost Benefit Analysis (CBA) of selected agroecological interventions within the two business models was also conducted. The BMC analysis helped actors in the selected business models to identify gaps that could be addressed to strengthen their business relationships. The B-ACT results show that the private processors performed better in terms of integration of the AEPs in their operational strategies (52.4%) compared to the public processor (32.8%). The private processors’ activities aligned better with principles that contribute to improved resource efficiency (76.2%) and strengthen resilience (55.6%). However, there is need to integrate more activities that contribute to secured social equity in their operations, which scored relatively low (25.6%). Farmers linked to the private processors also scored significantly high for most of the AEPs. Overall, these farmers scored 100% on resource use efficiency, 88.3% on resilience, and 52.2% on social equity. The public processor scored relatively low across most of the AEPs. It achieved a score of 49% on improved resource efficiency, 42% on securing social equity, and 7% on strengthening resilience. This means that the public processor needs to integrate more activities that strengthen resilience in its operations. Farmer groups supplying the public processor scored relatively high on principles that improve resource efficiency (85.7%). However, they performed relatively low on principles that contribute to securing social equity (20%). The CBA analysis of both business models show positive returns on investment with repayment periods ranging between two to four years for both farm and non-farm enterprises. On-farm interventions would take a shorter time (about two years) to breakeven than the business enterprises which would require three to four years. The outcomes and recommendations highlight strategies to enhance value creation, market access, and profitability within the mango value chain in Makueni County, and potential areas of intervention for agroecological transition.